The Impact of Intraoperative Microvascular Compromise on Outcomes in Microsurgical Breast Reconstruction - Chao, Albert H.; Coriddi, Michelle (Journal of Reconstructive Microsurgery, 2015)
Background In microsurgical breast reconstruction, the nature and fate of postoperative vascular compromise has been well studied, but limited data exist on intraoperative vascular compromise.Methods A review of all breast free flaps between 2007 and 2012 was performed. Details of intraoperative vascular compromise were recorded. Patients who experienced intraoperative microvascular compromise (Group I) were compared with patients who experienced only postoperative microvascular compromise (Group P) and all other patients (Group N).Results A total of 612 microsurgical breast reconstructions were reviewed. There were 73 (11.9%) flaps in Group I, 27 (4.4%) in Group P, and 512 (83.7%) in Group N. Compared with Group P, Group I more often involved arterial problems (p = 0.01), required supercharging for venous problems (p = 0.02), and was more likely to be salvaged (89.0 vs. 70.4%, p = 0.03). Group I had a similar overall complication rate compared with all other flaps (Group N + P) (31.5 vs. 27.1%, p = 0.49), but a higher flap loss rate (11.0 vs. 1.7%, p = 0.0003). The need to perform > 1 arterial revision was a risk factor for flap loss in Group I (p = 0.028). Total ischemia times > 175 minutes (p = 0.047) and reperfusion times > 80 minutes (p = 0.041) significantly increased the risk of flap loss to approximately 50%.Conclusion Intraoperative vascular problems occur more frequently than postoperative vascular problems but are more frequently salvaged. They do not increase the likelihood of reoperation or total complications compared with all other flaps but do increase the risk of flap loss.
Keywords: breast reconstruction; free flap; microsurgery